Reliability assessment based on hazard rate model for an embedded OSS porting‐phase. (17th March 2011) - Tamura, Yoshinobu; Yamada, Shigeru
SUMMARY Embedded Open Source Software (OSS) systems have been gaining a lot of attention in the embedded system area. The successful experience of embedded OSSs include Android, BusyBox, TRON, etc. Also, OSS market will be expanded not only to mobile phone OSS areas but also to other embedded OSS areas in the future. However, the poor handling of quality problem and customer support prohibit the progress of embedded OSS. Also, it is difficult for developers to assess the reliability and portability of embedded OSS on a single‐board computer. A method of software reliability assessment based on flexible hazard rate modeling for the embedded OSS is proposed in this paper. Also, several numerical examples are shown by using actual data. Moreover, this paper compares the proposed model with the conventional hazard rate models by using the comparison criteria of goodness‐of‐fit. Copyright © 2011 John Wiley & Sons, Ltd.